The Temperature-dependent Relative Self-Absorption technique: experimental setup and analysis simulation - Koseoglou, Pavlos; Prifti, Kiriaki; Isaak, Johann; Pietralla, Norbert; Cortés, Martha Liliana; Werner, Volker (HNPS Advances in Nuclear Physics, 2025)
In the present proceedings analysis simulations of the Temperature-dependent Relative Self-Absorption (TRSA) technique are presented together with the experimental setup developed at the Technische Universität Darmstadt dedicated for TRSA measurements. The analysis simulations show that precise level width measurements can be achieved, with uncertainties down to some parts per thousand